First true blood pressure measurement with micropulse detection of arterial opening achieved - Alan Murray; Dingchang Zheng; Clive J. Griffiths; Chengyu Liu; David J. Graham; Jeff Neasham; Adrian J. Cossor (Scientific Reports)
Abstract There is a well-accepted need for a new more accurate solution to automatic blood pressure measurement, in spite of clinical convenience continuing to encourage the adoption of oscillometric devices with their known poor accuracy throughout healthcare. Our solution avoids estimates, mathematical modelling, oscillometric algorithms, and inadequate calibration against numerous private clinical data sets. Here we show that our new technique detects, from an arm cuff, micropulses associated with arterial opening between systolic and diastolic pressures; hence detecting systole at the first micropulse and diastole at the last, during cuff deflation. Our technique has equivalent accuracy to the gold standard auscultatory method, and is significantly better than the requirements of the current international standard for blood pressure devices. Our results provide scientific evidence for the effectiveness of our technique, and demonstrate significant clinically important improvements. We anticipate that our technique can be automated easily and economically. We acknowledge that this early study is an initial manual evaluation, but expect this new technique to be an automated universal solution for true blood pressure measurement, and a vital step change in an important clinical measurement in healthcare of the worldwide population.